HOW TO MAP THE MEANING OF “SEE” IN KUPANG MALAY - Latuperissa, David Samuel (Lingual Journal of Language and Culture, 2016)
Lexicon ‘See’ as an English verb that means ‘perceive with the eyes’has different form of lexicon and different semantics meaning in Kupang Malay Language (KML). The lexicons that refer to ‘see’ are ‘lia’,‘loti’,‘malerok’, ‘maloi’ and‘pe’emata’. Those five lexicons have their own meaning. In order to understand those words deeply, such matters were analysed by a study using Natural Semantic Metalanguage (NSM) theory.By applying descriptive qualitative method and paraphrase/ explication technique, the slightly different semantic features of ‘lia’,‘loti’,‘malerok’, ‘maloi’ and‘pe’emata’ can be comprehensively revealed.
Keywords: KML, NSM, explication